2014
DOI: 10.4238/2014.april.29.6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of essential hypertension in a Mongolian population of China: a case-control study

Abstract: ABSTRACT. Lifestyle, habits, diet, and genetics are all important factors associated with the prevalence of hypertension. Many association studies have been performed in the Chinese Han population, whereas data explaining the high prevalence of hypertension in the Mongolian population remain scarce. In the present study, we aimed to determine the factors associated with the development of essential hypertension in Mongolians. A total of 194 hypertensive cases and 201 controls from Dongwu County were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Previous studies have found that the Chinese have lower BMI and higher BF% [37]. There were great differences in the diet and living habits of the Han and Mongolian ethnicities [38,39]. In comparison to the Han ethnicity, Mongolians had a higher meat and salt intake and a lower intake of fruits and vegetables, which meant that Mongolians ingested more fat and protein [40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the Chinese have lower BMI and higher BF% [37]. There were great differences in the diet and living habits of the Han and Mongolian ethnicities [38,39]. In comparison to the Han ethnicity, Mongolians had a higher meat and salt intake and a lower intake of fruits and vegetables, which meant that Mongolians ingested more fat and protein [40].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive sodium is a risk factor for hypertension which has been well documented in epidemiological [ 6 , 7 ] and clinical [ 8 , 9 ] studies. A previous meta-analysis included nine randomized, controlled trials with 14 comparisons between low and normal sodium intake groups [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The demographic and clinical characteristics between EH and NT showed that age, AC, BMI, TG, FBG were the risk factors, while HDL was the protective factor for EH, findings which were consistent with other researchers. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%